Apropos dental cryoanesthesia - Luis Antonio Lobo Cortés; Martha Leonor Rebolledo Cobos; Pedro Pablo Mejía Fernández (Editorial Ciencias Médicas, 2020)
Introduction: Cryoanesthesia is a type of topical anesthesia used in minor medical procedures. It is based on the descent or inhibition of the pain threshold caused by the thermal stimulus. Cryoanesthesia may be used in procedures performed on dental tissues to complement anesthetic drugs and combat anesthetic failure. Objective: Describe the findings about the use and application of cryoanesthesia in dental practice. Methods: An exploratory review was conducted of scientific and grey literature to evaluate pain reduction using cold temperatures without freezing the dental tissue. The databases consulted were Pubmed, Embase, Scopus, SciELO, Elsevier and Science Direct. The search in Google Scholar removed repeated entries and was limited to the first 100 results. The study covered the period extending from 1941 to December 2018, and used the PRISMA checklist to carry out the review. Results: Four papers were selected. All four used different devices, refrigerants and pain assessment scales. However, they all reported an absence of pain in some of their samples. Conclusion: Scant, outdated evidence was identified which contained discrepancies in the assessment scales, clinical protocols, refrigerant substances and devices used.